2018
DOI: 10.1021/acs.joc.7b02850
|View full text |Cite
|
Sign up to set email alerts
|

N-Thiocyanatosaccharin: A “Sweet” Electrophilic Thiocyanation Reagent and the Synthetic Applications

Abstract: N-Thiocyanatosaccharin (R) was readily prepared from the sweet additive Saccharin in two steps with a 71% overall yield. By applying this new reagent to diverse nucleophiles such as benzothiophenes, indoles, oxindoles, aromatic amines, phenols, β-keto carbonyl compounds, and aromatic ketones, a novel electrophilic thiocyanation reaction was achieved with high yields (up to 99%). The potential recycling of Saccharin, the wide scope of substrates, and the mild reaction conditions made this protocol much more pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 46 publications
0
51
0
2
Order By: Relevance
“…We further wished to explore this methodology with arylamines as substrates (Table ). Literature search revealed that para‐ selective C‐H thiocyanation of arylamines has been accomplished under metal free conditions using salts of thiocyanate in presence of oxidants such as CAN, K 2 S 2 O 8 , DDQ, H 2 O 2 , as well as by metal (Fe, Mn, and Cu) assisted catalysis. [11c], On applying the optimized reaction conditions to aniline ( 3a ), we observed that thiocyanation occurred exclusively at its para ‐position ( 4a ) though the reaction took longer time to complete (24 h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further wished to explore this methodology with arylamines as substrates (Table ). Literature search revealed that para‐ selective C‐H thiocyanation of arylamines has been accomplished under metal free conditions using salts of thiocyanate in presence of oxidants such as CAN, K 2 S 2 O 8 , DDQ, H 2 O 2 , as well as by metal (Fe, Mn, and Cu) assisted catalysis. [11c], On applying the optimized reaction conditions to aniline ( 3a ), we observed that thiocyanation occurred exclusively at its para ‐position ( 4a ) though the reaction took longer time to complete (24 h).…”
Section: Resultsmentioning
confidence: 99%
“…2‐Methyl‐4‐thiocyanatoaniline (4b): [19b] Yellow solid, hexane/EtOAc = 98:2, yield 68 % (112 mg), m.p. 68–70 °C; 1 H NMR: (400 MHz, CDCl 3 ) δ 2.15 (s, 3H), 3.88 (s, 2H), 6.66 (d, J = 8.16 Hz, 1H), 7.23–7.27 (m, 2H); 13 C NMR: (100 MHz, CDCl 3 ) δ 17.2 (CH 3 ), 109.4 (C), 112.5 (C), 115.7 (CH), 123.8 (C), 132.1 (CH), 135.0 (CH), 147.0 (C).…”
Section: Methodsmentioning
confidence: 99%
“…Aryl thio-and selenocyanates are versatile intermediates for various sulfur-and selenium-containing compounds that are of synthetic and biological interest [14][15][16][17][18][19][20][21][22][23][24][25][26]. Aryl thiocyanates are widely employed as building blocks in the synthesis of diverse sulfides [27,28], thiocarbamates [29], thionitriles [30], sulfonic acids [31], sulfonyl chlorides [32], thioesters [33], and sulfonyl cyanides [31] and mainly in the synthesis and functionalization of heterocyclic compounds [25,26,[34][35][36][37][38][39][40]. Particularly, selenium-containing organic compounds have recently attracted the interest of the scientific community due to their promising chemopreventive properties in connection with cancer therapy [32,[41][42][43][44], and also as antioxidant agents [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the reported approaches for the preparation of alkyl thiocyanates mainly focused on the nucleophilic [ 10 , 11 , 12 , 13 ] and electrophilic [ 14 , 15 , 16 ] substitution of prefunctionalized alkyl substrates with appropriated thiocyanation reagent and the direct thiocyanation of alkyl C–H bonds via oxidative functionalization [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, in these transformations, only a C–S bond is formed.…”
Section: Introductionmentioning
confidence: 99%